From Deals to Desires: The Mediating Role of Positive Emotions in the Relationship between Flash Sales, Free Shipping, and Impulsive Buying - Anggita Putri Indadari; M. Taufiq Noor Rokhman; Novita Rifaul Kirom (Petra International Journal of Business Studies, 2026)
This study examines the influence of flash sales and free shipping on impulsive buying among Generation Z Shopee users in Malang City, with positive emotions as a mediating variable. Data were collected through an online, structured questionnaire designed in Google Forms and distributed via WhatsApp and social media platforms (Instagram and TikTok). Respondent access was obtained through open participation links shared in student communities across three major universities in Malang. The questionnaire consisted of closed-ended items adapted from previous studies and measured using a 5-point Likert scale. A total of 190 valid responses were analyzed using SEM-PLS. The findings show that flash sales do not have a direct effect on impulsive buying, whereas free shipping does. Both flash sales and free shipping significantly enhance positive emotions, which strongly drive impulsive buying behavior. Positive emotion has also been shown to mediate the relationship between promotional strategies and impulsive buying. These results emphasize the central role of emotional responses in shaping spontaneous online purchasing decisions among Generation Z.